2015
DOI: 10.1074/jbc.m114.621128
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Dynamics of DNA Repair by Escherichia coli Endonuclease III

Abstract: Background: Endonuclease III is responsible for base excision repair of oxidized or reduced pyrimidine bases. Results: Stopped-flow kinetics analysis of endonuclease III interaction with DNA was performed. Conclusion: Endonuclease III uses a multistep mechanism of damage recognition, which likely involves Gln 41 and Leu 81 as lesion sensors. Significance: The results provide new insight into the mechanism of damage recognition by DNA glycosylases of the helixhairpin-helix-GPD structural superfamily.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 63 publications
0
36
0
Order By: Relevance
“…It is known that the fluorescence intensity of aPu in DNA depends on the fluorophore microenvironment changes, for example, as a result of local melting of the duplex in the immediate vicinity of the fluorophore [24-26]. In double-stranded DNA structures, during stacking interaction with neighboring bases, the fluorescence intensity of aPu residues reduces significantly in comparison with single-stranded DNA.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that the fluorescence intensity of aPu in DNA depends on the fluorophore microenvironment changes, for example, as a result of local melting of the duplex in the immediate vicinity of the fluorophore [24-26]. In double-stranded DNA structures, during stacking interaction with neighboring bases, the fluorescence intensity of aPu residues reduces significantly in comparison with single-stranded DNA.…”
Section: Resultsmentioning
confidence: 99%
“…Recent crystallographic [36, 37], kinetics [10, 38] and single molecule studies [9, 11] provide strong evidence that DNA glycosylases locate damaged DNA bases by one-dimensional diffusion along the DNA helix that is random, bidirectional, and is consistent with tracking rotationally along the DNA backbone. The Nth glycosylases rely upon the insertion of three amino acids into the DNA helix to stabilize the duplex upon eversion of the damaged base into the enzyme’s active site pocket and in EcoNth, these residues are Ile79, Leu81, and Gln41.…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism provides an explanation for how the Nth search might be independent of specific interactions within the binding pocket, allowing for recognition of a diverse set of substrates. A recent stopped-flow kinetics analysis showed Nth to induce several fast sequential conformational changes in DNA during binding, lesion recognition and forming the catalytically competent structure and that the first phase of non-specific binding may be insertion of Leu81 [10]. Of note, the EcoNth Leu81 residue counterpart in hNTHL1 is Phe181, which is bulkier, and may “sense” aromatic structures.…”
Section: Discussionmentioning
confidence: 99%
“…We substituted alanine for the wedge residue in each of these glycosylases, and in each case, the variant enzyme scanned along undamaged DNA at a significantly faster rate than the wild-type enzyme (Figure 3). In further support of the amino acid wedge being responsible for the lesion search, (Kuznetsov et al, 2015b) recently showed, using stopped flow kinetics, that the first phase of nonspecific binding of Nth to a lesion may be insertion of Leu81, its wedge residue.…”
Section: The Target Search On Undamaged Dnamentioning
confidence: 94%